2013
DOI: 10.7863/jum.2013.32.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Breast Mass Characterization Using 3‐Dimensional Automated Ultrasound as an Adjunct to Digital Breast Tomosynthesis

Abstract: Objective To retrospectively evaluate the effect of 3D automated ultrasound (3D-AUS) as an adjunct to digital breast tomosynthesis (DBT) on radiologists’ performance and confidence in discriminating malignant and benign breast masses. Methods Two-view DBT (CC and MLO or Lateral) and single-view 3D-AUS were acquired on 51 patients with (subsequently) biopsy-proven masses (13 malignant, 38 benign). Six experienced radiologists rated, on a 13-point scale, the likelihood of malignancy of an identified mass, firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Development of a compression paddle compatible for both x-ray and US imaging (152), selection of US coupling media, and breast coverage with US particularly at the breast periphery that is not in contact with the compression paddle have been reported (153). In an analysis of 51 patients with masses (13 malignancies), Padilla et al (154) reported similar AUCs for DBT alone and the combined DBT and automated breast US, and an improvement in discriminating masses from simple cysts.…”
Section: Multimodality Imagingmentioning
confidence: 61%
“…Development of a compression paddle compatible for both x-ray and US imaging (152), selection of US coupling media, and breast coverage with US particularly at the breast periphery that is not in contact with the compression paddle have been reported (153). In an analysis of 51 patients with masses (13 malignancies), Padilla et al (154) reported similar AUCs for DBT alone and the combined DBT and automated breast US, and an improvement in discriminating masses from simple cysts.…”
Section: Multimodality Imagingmentioning
confidence: 61%
“…Three-dimensional automated breast ultrasound has been developed to eliminate inter-performer variability and also to optimize workflow, since the exams are time consuming. CAD for 3D automated breast ultrasound is also in development [9]. Contrast enhanced ultrasound is currently being investigated to potentially assist in increasing sensitivity and specificity [10].…”
Section: Radiology: Advances In Screeningmentioning
confidence: 99%
“…In design two, researchers from the University of Michigan and GE Healthcare have essentially adapted design one and added digital breast tomosynthesis (DBT), a technology that enables 3D images of the breast to be reconstructed [2024]. In a study of 51 patients with biopsy-proven masses, Padilla et al [25] found no significant difference in receiver operating characteristic (ROC) performance when ABUS was added to DBT.…”
Section: Introductionmentioning
confidence: 99%